OPTIMALISASI LIMBAH TONGKOL JAGUNG SEBAGAI PAKAN TERNAK MELALUI IMPLEMENTASI PAKET TEKNOLOGI PENGOLAH PAKAN PADA KELOMPOK TANI SIDO MAKMUR II TULUNGAGUNG - Prabowo, Prayudi Setiawan; Wibowo, Theodorus Wiyanto; Tukiran, Tukiran; Pangestu, Puji Dwi; Pambudi, Rizdana Galih (LPPM Universitas Bina Bangsa, 2025)
The corn plant has become a favorite of the farmer group “SIDO MAKMUR II” because it is resistant to pest attacks, suitable for planting in the dry season, and easy to maintain, providing significant benefits to farmers. However, the utilization of corn plant parts has not been maximized, particularly the use of corn cobs, which remains unexploited by the “SIDO MAKMUR II” group. According to Mr. Nurkolis, it is indeed unfortunate that corn cobs are either discarded or not utilized, given that this waste can be processed into high-quality animal feed. This is largely due to a lack of adequate tools and appropriate technology, as well as management issues, especially in bookkeeping for the business. To address these issues, the Community Partnership Empowerment Team from Universitas Negeri Surabaya is working to optimize corn cob waste as animal feed, aiming to resolve production problems in utilizing corn cob waste and issues in business management, particularly in savings and loans. The proposed solutions include (1) procuring and implementing a package of machines for processing corn cob waste into animal feed, (2) training on creating powdered corn cob feed through fermentation, and (3) training and assistance in implementing savings and loan management for the partners. The results of this community service activity, through the implementation of a technology package for processing corn cob waste into animal feed, show that the “SIDO MAKMUR II” group can now process corn cobs into animal feed using grinding and milling machines, as well as a ribbon screw mixer equipped with a timer and speed control. Additionally, there has been an improvement in management, particularly in the group’s finances, due to the establishment and training in business management.